Muslim youths’ satisfaction toward Muslim-friendly hotels: examining the effects of hotel image, brand image and employee performance - Abdul Latif, Samshul Amry; Adnan, Nur Adilah (Springer Nature, 2020)
This paper aims to examine the effects of hotel image, brand image and employee performance on customer satisfaction of Muslim youths during their leisure stay in Muslim-friendly (MF) hotels in Malaysia. Self-administered questionnaires measuring hotel image, brand image, employee performance and customer satisfaction on a five-point Likert scale were distributed to 300 tourists in four prominent hotels in Kuala Terengganu. The data is then analyzed by multiple regression using SPSS software. The results indicated that hotel image and employee performance were found to be significant factors in predicting Muslim youth’s customer satisfaction of their hotel accommodation and hospitality services in MF hotels. However, brand image was found to be an insignificant predictor to their satisfaction. The sample of this study was limited to only Muslims, and mainly students. However, this does not suggest that students should be ignored in terms of their purchasing power and preference. Future studies may want to include other consumer segments and examine other MF hotels or hotels with similar concepts in countries interested to tap on the Muslim tourists, for example, Japan, China and Korea among others. Malaysia is known to be an MF destination among tourists from many parts of the world. By understanding Muslim consumers’ expectations, the performance of hotel employees and hotel image can be utilized by hotel operators worldwide to enhance their marketing strategies.